Financial Governance and its Role in Territorial Development: An Analytical Study of Tangier Municipality’s Structural Budget (International Journal of Financial, Administrative and Economic Sciences, 2026)
The finances of local authorities occupy a crucial and pivotal position in their management, serving as the primary means of implementing economic, social, cultural, and environmental policies at the local level. They are the lifeblood of elected councils and the driving force behind their administration. They are "the instrument through which these programs are implemented, all local facilities are financed, public infrastructure is constructed, and elected councils translate their work programs into tangible reality" (Al-Arfi H., 2018, p. 5). Local authority revenues constitute a fundamental component of the local budget and a determinant of the implementation of local programs. The extent of a local authority's intervention is proportional to the size of its budget; its intervention in fulfilling its developmental function increases with the size of its budget and decreases with its reduction. Given its importance, the legislator granted local councils autonomy in managing their finances and supported them with a reformed local tax system that serves local authorities, as stipulated by Law 06-47 and Law 07-39, which regulate fees, charges, contributions, and levies of a non-tax nature (Royal Decree, 2007). From this perspective, it is accurate to say that the financial resources of a local authority are among the most important criteria for evaluating management interventions and measuring their effectiveness, as they reflect and demonstrate the level of local governance.
Keywords: Financial Governance; Lever for Territorial Development; Structural Budget; Local Authority; Tangier